Flags of the Night Sky When Astronomy Meets National Pride - Bordeleau, André G. (Springer New York : Imprint: Springer, 2014)
Many national flags display astronomical features–Sun, Moon, stars–but are they really based on existing astronomical objects? The United States flag sports 50 stars, one for each state, however none of them are linked to real stars. Further, the lunar crescent is often shaped like the Sun being eclipsed by the Moon. At times, stars are seen right next to the crescent, where the darkened disc of the moon should be! This book will present true astronomical objects and patterns highlighted on national flags and link informative capsules about these objects to the political reasons why they were chosen to adorn such an important symbol.